Effectiveness of different means of disinfection against soil foci of anthrax (Bacillus anthracis) burials at a depth of up to 3.5 m: an experimental study - Vladislava Suchshikh; Abdilkarim Karimov; Malik Yussupov; Batyrbek Aitzhanov; Aspen Abutalip; Assiya Mussayeva; Natalya Yegorova; Saltanat Mamanova; Begali Kanatov (Caspian Journal of Environmental Sciences)
There are over 2,000 anthrax-infected soil foci in Kazakhstan, posing a potential threat of infection with anthrax to the population. The anthrax soil foci are found in all regions of Kazakhstan, often located near residential buildings, interfering with the promising development of the region. Experimental work was carried out on the development of disinfection of the deep soil layers at a depth of up to 3.5 m using the drilling method. The experiments were carried out on a modular site measuring 210 cm by 280 cm with a natural occurrence of soil. The experimental site disinfection method included the complete filling of 12 prepared wells with BA-12 disinfectant. The soil in the wells had been previously contaminated with a vaccine culture of anthrax (Bacillus anthracis) pathogen 55-VNIIVViM. The total volume of the disinfectant solution required for complete disinfection of the entire volume of the soil (the experimental site, amounted to 1,635 L) was determined. According to the authors, the main practical conclusion of the study was the possibility to use the scheme of disinfection of soil foci of anthrax burials developed during the experiment for carrying out production and construction work at the site of existing burials.